2008
DOI: 10.1111/j.1365-2923.2008.03091.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping efficacy and perceived family support: potential factors for reducing stress in premedical students

Abstract: Findings from the present study indicate that perceived family support plays a key role in establishing premedical students' confidence in their ability to cope with the challenges of academic life. These findings have important implications for further studies on coping and stress in premedical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 17 publications
1
24
0
3
Order By: Relevance
“…These students all had a positive and supportive family background. Perceived family support has been shown to reduce stress in premedical students (Klink et al 2007) and in our study, it also seems to be of importance. One could argue that these students survived their undergraduate studies despite their lack of generic skills and that the 'survival' skills they acquired enabled them to have a predominantly engaging postgraduate experience.…”
Section: Discussionmentioning
confidence: 63%
“…These students all had a positive and supportive family background. Perceived family support has been shown to reduce stress in premedical students (Klink et al 2007) and in our study, it also seems to be of importance. One could argue that these students survived their undergraduate studies despite their lack of generic skills and that the 'survival' skills they acquired enabled them to have a predominantly engaging postgraduate experience.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, salient socioeconomic reasons should also be considered, such as parents' more selective and strategic placing of sons, relative to those of daughters, in the job markets and, as a consequence, higher parental expectations set in and greater family pressure exerted on sons, in order to ensure that the parental occupational status and specific profession is ensured in the following generation. Clearly, these quite different lines of explanation would be hard to disentangle, but perhaps this may not be essential here, as it appears more conceivable, especially from the view of the literature on the still prevalent lack of gender equity in medicine (see Bickel 2001;Reed and Buddeberg-Fischer 2001;Riska 2001;Kilminster et al 2007;Klink et al 2008), that an intricate and mutually amplifying interplay of all these factors contributes to the observed outcome of a marked patrilateral effect in the familial aggregation of the medical profession. The specific pattern of familial aggregation of physicians among medical students observed here might also be taken as suggestive for some increase of the familial-aggregation effect in the more recent generations, as compared to previous ones.…”
Section: Discussionmentioning
confidence: 89%
“…Common knowns from these much broader literatures include the following: social mobility studies have found that upward mobility into the medical profession from outside is aggravated, as the risk of unsuccessful application to medical schools is higher among those not having a medical family history (e.g., McManus and Richards 1984). Also, study progress in this group has been found to be less favorable than in students with medical relatives (Haidet et al 2002;Klink et al 2008). Among other findings, accounts on the sociology and history of the medical profession especially evidence the high social prestige and status this profession enjoys in the general population (Furnham 1986).…”
mentioning
confidence: 96%
“…Third, most university students report regular contacts with their family when they are in their early academic years; and, when dealing with academic challenges, students report their families to be their number-one source of support (Stecker, 2004). Finally, Klink, Byars-Winston, and Bakken (2008) found that students' levels of family support were related to their confidence in their capacity to deal with challenging academic experiences.…”
Section: Family Support and Academic Performancementioning
confidence: 85%